PEMBERIAN STATUS TERHADAP TERORIS BERDASARKAN KONVENSI JENEWA - Grace Natalia Kusuma; Tiffany Setyo Pratiwi (LPPM Universitas Abdurrab, 2020)
This research analyzes about the status that given towards terrorists according to the Geneva Conventions as a source of International Humanitarian Law. This research is using descriptive qualitative methods to describe the practices carried out by terrorists and violations committed against the International Humanitarian Law. The sources for this research are from literature studies with secondary data sources such as books, articles, research journals, mass media, college notes, and internet sites. This research describing that according to the Geneva Conventions, the status given to terrorists as perpetrators of crimes against humanity is unlawful combatant. In addition, the ICRC also gives unprivileged belligerent status to those who carry out their acts of terrorist as individuals and do not have assimilation with any terrorism groups. Acts of terrorism have also been proven to violates the Geneva Conventions, including Article 33 and Article 147 of the Geneva Convention IV 1949, Articles 51 and 85 of Additional Protocol I 1977, and Article 13 of Additional Protocol II 1977.